2015
DOI: 10.1002/2015jd023419
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time measurements of ambient aerosols in a polluted Indian city: Sources, characteristics, and processing of organic aerosols during foggy and nonfoggy periods

Abstract: A detailed time-resolved chemical characterization of ambient nonrefractory submicron aerosols (NR-PM 1 ) was conducted for the first time in India. The measurements were performed during the winter (November 2011 to January 2012) in a heavily polluted city of Kanpur, which is situated in the Indo-Gangetic Plain. Real-time measurements provided new insights into the sources and evolution of organic aerosols (OA) that could not be obtained using previously deployed filter-based measurements at this site. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 103 publications
(149 reference statements)
10
66
3
Order By: Relevance
“…These results support the notion that aqueous processing plays a more important role in haze formation under high RH conditions and that it tends to form more large particles. The enhancement of SOA production via aqueousphase chemistry has been observed in many previous field studies (Ge et al, 2012;Chakraborty et al, 2015;. As discussed above, SOA in this study shows a good correlation with [SO 2− 4 + NO − 3 ] and particle water (under high RH levels), indicating that aqueous chemistry during foggy days might facilitate the production of both SNA and SOA Xu et al, 2017b).…”
Section: Specific Episodes Analysis (Ep2 and Ep5)supporting
confidence: 82%
See 1 more Smart Citation
“…These results support the notion that aqueous processing plays a more important role in haze formation under high RH conditions and that it tends to form more large particles. The enhancement of SOA production via aqueousphase chemistry has been observed in many previous field studies (Ge et al, 2012;Chakraborty et al, 2015;. As discussed above, SOA in this study shows a good correlation with [SO 2− 4 + NO − 3 ] and particle water (under high RH levels), indicating that aqueous chemistry during foggy days might facilitate the production of both SNA and SOA Xu et al, 2017b).…”
Section: Specific Episodes Analysis (Ep2 and Ep5)supporting
confidence: 82%
“…This result indicates different formation mechanisms of SOA between the two different episodes. Chakraborty et al (2015) have also observed similar aerosol composition differences between foggy and non-foggy events with a high-resolution aerosol mass spectrometer instrument deployed in Kanpur, India. While photochemical processing is the major formation mechanism of Ep2, aqueous-phase processing is more important for the formation of more aged SOA.…”
Section: Specific Episodes Analysis (Ep2 and Ep5)supporting
confidence: 54%
“…During the Kanpur collocation, relative fractions among the major species CM, sea salt, ASO 4 , and ANO 3 all matched well with previous studies (Behera and Sharma, 2010;Chakraborty et al, 2015;Ram et al, 2012) that also sampled during winter dry seasons. Chakraborty et al (2015) measured 70 % organic mass composition and found a combined mass of 28 % for ASO 4 + ANO 3 compared to SPAR-TAN mass (26 %).…”
Section: Kanpur India (N = 33)supporting
confidence: 76%
“…Chakraborty et al (2015) measured 70 % organic mass composition and found a combined mass of 28 % for ASO 4 + ANO 3 compared to SPAR-TAN mass (26 %). SPARTAN ASO 4 (19 %) compares well to 13 % of Ram et al (2012) and 18 % for Behera and Sharma (2010), and ANO 3 (7.4 %) is close to previous values (6.1 and 6.6 %).…”
Section: Kanpur India (N = 33)mentioning
confidence: 99%
“…If we couple now these information's with the atmospheric condition as discussed above, it can be inferred that during the post-foggy days (by-and-large in II campaign), the WSOC/OC ratio was higher but OC/PM 2.5 was lower as compared to that during the non-post-foggy day condition (mostly in I campaign). A quite similar observation has been reported earlier based on HR-TOF-MS (highresolution time-of-flight aerosol mass spectrometer) from central IGP location at Kanpur (Chakraborty et al 2015). Their study has observed a decrease of ~ 5% (nearly similar to that observed herein of 6% difference) in OC mass fraction (in PM 1 ) during the post-foggy events as compared to that during non-post-foggy events.…”
Section: Influence Of Fog On Organic Aerosol Compositionsupporting
confidence: 75%